231k views
0 votes
Solve the following equation. -4y+8=4(2y-3)-2(-16+8y)

a) y= -4
b) y= 4
c) y= -2
d) y= -6


Thank you so much!!!

2 Answers

3 votes

Answer:

y = 3

Step-by-step explanation:

-4y + 8 = 4(2y - 3) - 2(-16 + 8y) use distributive property

-4y + 8 = (4)(2y) + (4)(-3) + (-2)(-16) + (-2)(8y)

-4y + 8 = 8y - 12 + 32 - 16y combine like terms

-4y + 8 = (8y - 16y) + (-12 + 32)

-4y + 8 = -8y + 20 subtract 8 from both sides

-4y = -8y + 12 add 8y to both sides

4y = 12 divide both sides by 4

y = 3

User AsifHabib
by
5.2k points
6 votes

Answer:

are you sure you wrote the answers right? because when i solve it i get y=3

Step-by-step explanation:

distributive property

-4y + 8 = 8y - 12 + 32 - 16y

combine like terms

-4y + 8 = -8y + 20

subtract 8 on both sides

-4y = -8y + 12

add -8y on both sides

4y = 12

simplify (division)

y= 3

User Morgan
by
6.2k points